Pengembangan Modul IPA SMP Pada Materi Sistem Reproduksi Manusia Berbasis Literasi Sains - Muna, Bahzatul (Interdisciplinary Explorations in Research Journal, 2026)
This research was conducted to develop learning modules on human reproductive system materials based on science literacy for junior high school students. The development procedure uses a 3D model, namely with several stages: the Define stage, the Design stage, and the Develop stage. The instruments in this study are module validation sheets and student learning outcome test validation sheets. The validity test uses a likert scale with four categories, namely very lacking, lacking, good and very good. Validity testing is carried out by 4 expert validators. The test results on the module show that the module is validated in the valid category without revision with a percentage of 85.85%. The test results on the student learning outcome test instrument showed that the development test instrument was validated in the valid category with a small revision with a percentage of 84.75%. Modules that have been validated can be used in the next stage of the development process, namely the application of the product to the learning process in schools.